Pojęcie „dysocjacji” – zagadnienia podstawowe - Jedlecka, Wioletta (Filozofia Publiczna i Edukacja Demokratyczna, 2014)
In this article I present the notion the dissociation. The dissociation is connected with personality disorders and with the trauma. Experience a strong trauma is nature of dissociative disorders. The dissociation can have different manifestations, e.g. the amnesia, the confusion or the exchange of the personality. Dissociative disorders are not only the domain of the so-called pediatric pathology. Dissociation is also a mechanism activated during invasive medical procedures that the experience can touch every family.